2019
DOI: 10.1177/2151459318808164
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Questionnaire Is Not a Strong Prognostic Factor for Functional Outcomes in Hip or Knee Arthroplasty Patients

Abstract: Introduction:Up to 33% and 25% of patients with end-stage hip and knee osteoarthritis (OA) are considered frail by the Groningen Frailty Indicator (GFI). This study aims to assess whether frail patients have lower functional gains after arthroplasty and to assess GFI as a tool to discriminate between good and adverse change score.Materials and Methods:Patients with end-stage hip/knee OA scheduled for arthroplasty were recruited from the Longitudinal Leiden Orthopaedics Outcomes of Osteo-Arthritis Study. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“… 40 , 41 However, an earlier study demonstrated that the improvement in functional scores was similar for both frail and non-frail patients despite the older median age in the frailty group. The current study found that residual frailty following THA and TKA was significantly associated with older age, 7 but the associations remain controversial. Further studies are needed to assess the effect of age on improving frailty as a prognostic factor in OA patients following THA and TKA.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“… 40 , 41 However, an earlier study demonstrated that the improvement in functional scores was similar for both frail and non-frail patients despite the older median age in the frailty group. The current study found that residual frailty following THA and TKA was significantly associated with older age, 7 but the associations remain controversial. Further studies are needed to assess the effect of age on improving frailty as a prognostic factor in OA patients following THA and TKA.…”
Section: Discussionmentioning
confidence: 71%
“…In previous research, frail patients with OA had more adverse events in daily activities after THA and TKA; consequently, they had an increased dependence on outside help, and a decrease in IADL and HRQoL. 32 , 33 Reportedlly, total joint arthroplasty for hip and knee OA is highly effective in relieving pain and improving physical function, 7 , 34 , 35 which is supported by our findings showing significant improvement in pain, IADL, and HRQoL at 6 months after surgery. We also found that frailty in patients was significantly decreased from 57.4 to 38.2% by THA and TKA procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relationships of gender, alcohol consumption, socioeconomic status, allergy, and vitamin D insufficiency and functional outcome after THA are unclear [22]. Meessen et al [23] studied the impact of frailty (Groningen Frailty Indicator, GFI) on the functional outcomes after THA and total knee arthroplasty (TKA). In the regression analysis, the GFI had limited ability to affect the functional outcome change (HOOS) in THA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meessen et al [ 23 ] studied the impact of frailty (Groningen Frailty Indicator, GFI) on the functional outcomes after THA and total knee arthroplasty (TKA). In the regression analysis, the GFI had limited ability to affect the functional outcome change (HOOS) in THA patients.…”
Section: Discussionmentioning
confidence: 99%